Vůz pro přepravu eurokošů - Štěpán, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Cílem této bakalářské práce je návrh a konstrukce tažených vozíku pro eurokoše a jiné paletové jednotky. Tato práce je zaměřena na přehled současných produktů, na konstrukci vozíku a stanovení geometrie a konstrukce řízení.

The objective of this bachelor thesis is design and construction of towed vehicle for eurocontainers and other pallet units. This thesis is aimed to on overview of present products, vehicle construction and determination of geometry and construction of steering.
Vehicle for transport of eurocontainer
Keywords: Vozík; logistický vlak; eurokoš; řízení; logistika; manipulační technika; Vehicle; logistics train; eurocontainer; steering; logistics; handling machine